2019
DOI: 10.1038/s41467-019-10830-9
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic p38α MAPK drives NMDA receptor-dependent long-term depression and modulates long-term memory

Abstract: NMDA receptor-dependent long-term depression (LTD) in the hippocampus is a well-known form of synaptic plasticity that has been linked to different cognitive functions. The core mechanism for this form of plasticity is thought to be entirely neuronal. However, we now demonstrate that astrocytic activity drives LTD at CA3-CA1 synapses. We have found that LTD induction enhances astrocyte-to-neuron communication mediated by glutamate, and that Ca 2+ signaling and SNARE-dependent vesicular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 73 publications
6
82
0
Order By: Relevance
“…It was reported that the NLRP3 in ammasome modulated MAPK signaling pathway in depressive mice [40]. In conclusion, we are consistent with the previous study that protein phosphorylation and MAPK signaling pathway were known to potential depression-related pathogenesis [41,42].…”
Section: Discussionsupporting
confidence: 93%
“…It was reported that the NLRP3 in ammasome modulated MAPK signaling pathway in depressive mice [40]. In conclusion, we are consistent with the previous study that protein phosphorylation and MAPK signaling pathway were known to potential depression-related pathogenesis [41,42].…”
Section: Discussionsupporting
confidence: 93%
“…Our data showed that these DEGs were mainly enriched in the neurotrophin signaling pathway, insulin signaling pathway, alcoholism, GABAergic synapse, glutamatergic synapse, amphetamine addiction, MAPK signaling pathway, PI3K‐Akt signaling pathway and circadian rhythm (Table ). Interestingly, these signaling pathways are involved in the pathophysiology and treatment of depression . For example, GABA and glutamate neurotransmitter deficits are used to explain the neurobiological abnormalities associated with MDD, which has been well‐accepted .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that a specific genetic ablation of the p38α isoform virtually abolishes NMDA-dependent LTD when targeting astrocytes, while producing no effect or slightly enhancing LTD when targeting neurons. These data indicate that astrocytic p38α is involved in activity-dependent glutamate release from astrocytes, contributing to astrocyte-to-neuron communication [39]. The authors concluded that the activity of p38α MAPK in the astrocyte contributes to hippocampal NMDA-dependent LTD, and is capable of modulating long-term memory in vivo [39].…”
Section: P38 Mapk and Synaptic Functionmentioning
confidence: 99%